‘Kein ästhetisches Heil, außer im Alterswert?’: Over het actuele Duitse reconstructiedebat (Bulletin KNOB, 2015)
The cultural heritage institutions in the Netherlands have traditionally taken a dim view of the reconstruction of heritage buildings when most or all of the material substance has been lost. Recent discussions about, for example, the listed status of the reconstructed mill at Burum (destroyed by fire in 2012) or the possible reconstruction of the nineteenth-century attic of Artis’s Ledenlokalen (damaged during World War II) illustrate that the guiding principles of the institutional heritage sector do not seem to meet the actual challenges arising from the quest for reconstruction. There is a need for in-depth investigations and theoretical reflections on this topic, yet these are rare at present in the Netherlands. Hence this article takes a closer look at Germany where – in reaction to an increasing number of reconstruction initiatives, such as the Berlin Palace or the Neumarkt/Frauenkirche in Dresden – some noteworthy research projects have been conducted in recent years. First and foremost is Geschichte der Rekonstruktion – Konstruktion der Geschichte, an extensive study by a group of scholars led by Winfried Nerdinger and Uta Hassler. Based on a large corpus of reconstruction cases from different time periods dating back to the classical age, they concluded that the act of restoring a structure to an earlier, lost state using new materials has a long cultural history. The case-study analysis also revealed that while the motives for reconstruction are quite stable over the centuries, the paradigms and techniques for the preservation of ancient monuments are historically determined.The publication and exhibition of the research results provoked fierce protests from German heritage professionals who feared that these conclusions might pressurize them to abandon their reserved attitude towards reconstruction. Their line of argumentation mainly followed the guiding principles of the founding fathers of the modern heritage preservation movement, including Alois Riegl and Georg Dehio. The dispute generated an anthology of interesting key texts, but it also demonstrated that clinging to a theoretical framework established over a hundred years ago can blind one to relevant topics for in-depth research within the field of heritage preservation, such as the question of how and to what extent different target groups should be informed about the reconstruction of (parts of) a building. Another promising line of investigation concerns the various heritage values related to the topic of reconstruction – think of traditional values like the beeldwaarde (image) or recently established ones like the belevingswaarde (experience) and nostalgiewaarde (nostalgia) – and their shift in meaning over time.